Pemanfaatan bot telegram untuk pembelajaran bahasa secara daring - Hasanah, Uswatun (2020)
In this pandemic situation because of Covid-19, it forces teachers and students should work and study from home. Therefore, innovation in teaching and learning is done by the teachers to make it more effective and interactive. In fact, using many applications for online learning makes students getting some problems. They need more internet data and space in their devices for accessing many apps or downloading learning materials such as pictures, audios or videos. In this case, telegram is the app for online learning that can be maximized by making telegram Bot. The aim of this study was to explore how telegram Bots could be used in teaching and learning process and how the feedback of the students as the users. This study used qualitative method. Data were collected by documentation, analyzing and interviewing. The result of the study is English teaching and learning process to be more effective by using telegram Bot. Students responded that the English teaching and learning using Bot telegram is really fun, interesting and easy to be used. They do not need for downloading many apps or learning materials.